High-Q Plasmonic Fano Resonance for Multiband Surface-Enhanced Infrared Absorption of Molecular Vibrational Sensing - Dayal, Govind (2017)
Realizing strong plasmon–vibration interactions between infrared-active vibrational bands and resonating plasmonic metasurfaces opens up the possibilities for ultrasensitive label-free detection of chemical and biological agents. The key prerequisites for exploiting strong plasmon–vibration interactions in practical spectroscopy are structures, which provide giant field enhancement that highly depends on the line-width and line-shape of the plasmonic resonances supported by these structures. Here, multiband surface-enhanced infrared absorption (SEIRA) of poly(methyl methacrylate) (PMMA) is demonstrated. The line-width and line-shape of the proposed plasmonic metasurface can be readily tuned to match the multiple vibrational modes of the PMMA to sense the prohibitively weak fingerprints. The tightly coupled system exhibits mode splitting in the optical spectrum resulting in new hybrid plasmon–phonon modes of PMMA. Such a strong interaction of high-Q Fano resonances to multiple phonon modes in ultrathin film analytes over a broadband spectral range could be step forward towards ultrasensitive sensing of biological and chemical molecules.